Becoming an inventor: a young Latina’s narrative - Sáenz, Cristina; Skukauskaitė, Audra; Sullivan, Michelle (Frontiers in Education, 2024)
Latinas, along with many other minoritized groups, are underrepresented as inventors in the United States. Despite accounting for over 9% of the population, <1% of U.S. patent holders are Latina. In an effort to increase diversity among inventors and patent holders, a number of K-12 programs have been created to provide opportunities for students to participate in the iterative and recursive processes of inventing. One example is the emerging field of invention education. Invention education is an educational approach which teaches students how to identify and solve problems within their communities. Little is known about the experiences of Latina students who have participated in invention education and have begun developing identities as inventors. Through narrative methodology, we analyzed how the life experiences of one Latina student contributed to her identity development as an inventor. Four themes were developed through the analysis of the Latina student’s narrative. The first was the early and consistent support of her family members. The second theme was the student’s understanding of the importance of Latinx representation in STEM. The student’s participation in extracurricular STEM activities was the third theme that contributed to the development of her identity as an inventor. The final theme was her continued involvement in engineering at the university level. While early, consistent, and continued identity work in extracurricular invention and STEM activities contributed to the development of an inventor’s identity, literature has shown that opportunities such as these are not available to all students, especially those who have been historically underrepresented as inventors. We argue for making access to invention education more equitable by embedding it within the school day.